Sexual behaviour of women in rural South Africa: a descriptive study - Jan Henk Dubbink; Lisette van der Eem; James A. McIntyre; Nontembeko Mbambazela; Geoffrey A. Jobson; Sander Ouburg; Servaas A. Morre; Helen E. Struthers; Remco P. H. Peters (BMC, 2016)
Abstract Background Sexual behaviour is a core determinant of the HIV and sexually transmitted infection (STI) epidemics in women living in rural South Africa. Knowledge of sexual behaviour in these areas is limited, but constitutes essential information for a combination prevention approach of behavioural change and biomedical interventions. Methods This descriptive study was conducted in rural Mopani District, South Africa, as part of a larger study on STI. Women of reproductive age (18-49 years) who reported sexual activity were included regardless of the reason for visiting the facility. Questionnaires were administered to 570 women. We report sexual behaviour by age group, ethnic group and self-reported HIV status. Results Young women (<25 years) were more likely to visit bars, practice fellatio, have concurrent sexual partners and report a circumcised partner than older women (>34 years); there was no difference for condom use during last sex act (36 % overall). Sotho women were more likely to report concurrent sexual partners whereas Shangaan women reported more frequent intravaginal cleansing and vaginal scarring practice in our analysis. HIV-infected women were older, had a higher number of lifetime sexual partners, reported more frequent condom use during the last sex act and were more likely to have a known HIV-infected partner than women without HIV infection; hormonal contraceptive use, fellatio, and a circumcised partner were less often reported. Conclusions This study provides insight into women's sexual behaviour in a rural South African region. There are important differences in sexual behaviour by age group and ethnicity and HIV status; these should be taken into account when designing tailor-made prevention packages.